The Use of Augmented Reality in History Education: A Study on Conceptual Understanding Effects - Priyono, Cipto Duwi; Sok, Vann; Souza, Felipe (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Technology integration in education has opened new avenues for enhancing student engagement and learning outcomes. Augmented Reality (AR) is a technology that offers immersive and interactive learning experiences, particularly in subjects like history, where visual and spatial understanding is crucial. ws and teacher observations to gain deeper insights into the learning experiences. The results indicated a significant improvement in the conceptual understanding of history in the experimental group compared to the control group. Students using AR demonstrated a better ability to visualize historical events, understand complex historical contexts, and establish connections between historical periods. Qualitative data supported these findings, with students reporting higher engagement and enjoyment in learning history through AR. The study concludes that AR can significantly enhance conceptual understanding in history education. AR-based learning tools offer a promising alternative to traditional methods by providing immersive and interactive experiences that engage students and deepen their understanding of historical concepts. These findings suggest that integrating AR into history curricula can be a valuable strategy for improving educational outcomes.